THE IMPROVEMENT OF MARRIAGE REGISTRATION SERVICES IN THE OFFICE OF RELIGIOUS AFFAIRS OF SAYUNG SUBDISTRICT TO PROVIDE SOCIAL WELFARE - Sri Wahyuningsih (UNISSULA, 2017)
Along with the importance of the registration of marriage, the existence of Office of Religious Affairs is a part of a local government institution that is assigned to provide services to the community. In this matter, each state organizer has an obligation to provide excellent public services, meaning that the services provided by the government should be able to provide satisfaction to the community. This article aims at discussing some efforts to improve the service of marriage registration in the Office of Religious Affairs located in Sayung, Demak, Central Java. This research uses a descriptive qualitative method based on five service dimensions. The interview, observation and documentation are conducted to gather data. The result reveals that the quality of marriage registration service in the Office of Religious Affairs, Sayung has not been achieved ultimately. In fact, the Office of Religious Affairs, Sayung does not have a minimum service standard so that people cannot assess the service standard of marriage registration clearly. Therefore, in order to improve the service of marriage registration, the officers in the Office of Religious Affairs, Sayung need to improve the quality of marriage registration services that can be achieved by completing a clear minimum service standard.Keywords: Office of Religious Affairs, Service, Marriage Registration